Soil organic carbon stock and fractional distribution in upland grasslands - Eze, Samuel; Palmer, Sheila M.; Chapman, Pippa J. (Geoderma, 2018)
Upland grassland soils are an important terrestrial carbon (C) store and provide vital ecosystem services such as climate regulation. The C stocks in these soils are subject to changes due to management activities. In this study, we compared soil organic C (SOC) stocks and fractions under traditional hay meadow and conventional (silage or permanent) pasture management regimes at two upland grassland locations within the Yorkshire Dales, northern England, United Kingdom. Stocks of SOC in the top 15cm of the grassland soils were determined from bulk soil samples and in soil fractions after a combination of physical and chemical fractionation. Results showed that these upland grasslands stored significant amounts of organic C in the top 15cm of their soils, ranging from 58.93±3.50 to 100.69±8.64Mgha−1. Overall, there was little contrast between the sites except that soil C stock was significantly higher under the Nidderdale silage pasture that received the highest nitrogen (N) inputs, possibly due to enhanced vegetation growth and subsequent litter return to the soil. No effect of soil parent material was observed on soil C stock due to liming-induced increase in the pH of Nidderdale soils and neither management activities nor soil parent materials affected the distribution of soil C into different fractions. In all sites, about 70% of the SOC stock was protected in stable soil fractions, specifically in the mineral soil mass, indicating a potential for the grasslands to contribute in climate change mitigation. However, due to the rapid turnover of the labile C pool and especially in a changing climate, it is recommended that further research be carried out in order to understand the turnover rates of labile C pools and whether management activities alter the distribution between the decomposition products. This will help to better understand whether rapid turnover of labile C will negate the likely benefits of stable C pools to climate change mitigation. •Upland grassland soils store significant amounts of carbon (C).•Nitrogen addition increases soil C stock in upland grasslands.•Distribution of soil C fractions determines their stability.•Higher soil C stock in stable forms is beneficial to climate mitigation.•Higher proportion of active soil C has implication for climate feedback.